NEGOTIATING WORLDS, WORDS AND IDENTITIES: SCAFFOLDED LITERACIES FOR PRE-SERVICE TEACHERS AND CHILDREN - Cumming-Potvin, Wendy Marie (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2013)
Aiming to extend sociocultural theory about the teaching and learning of literacies, this article reports on data from a qualitative study underpinned by a sociocultural framework (Rogoff, 1990; Vygotsky, 1986). Conducted in an Australian university community, the project tracked a group of pre-service teachers engaging in scaffolded literacy events, such as face-to-face and on-line discussions and shared reading experiences with children. Highlighting the importance of examining the teaching and learning of literacies across formal and informal settings, results offer information about how these pre-service teachers constructed understandings and situated identities (Gee, 1990, 2000-2001) through scaffolding. Pedagogical implications for pre-service teacher education are discussed. NÉGOCIER LES MONDES, LES MOTS ET LES IDENTITÉS: SOUTIEN À L’APPRENTISSAGE DES LITTÉRATIES POUR LES FUTURS ENSEIGNANTS ET LES ENFANTS L’objectif de cet article est d’élargir la portée de la théorie socioculturelle de l’enseignement et de l’apprentissage de la littératie. Il fait le compte-rendu des données tirées d’une étude qualitative étayée dans un cadre socioculturel (Rogoff, 1990; Vygotsky, 1986). Pilotée par une communauté universitaire d’Australie, ce projet a suivi un groupe de futurs enseignants participant à des événements de soutien à l’apprentissage de la littératie, telles que des discussions face à face et en ligne ainsi que des expériences de lecture partagée avec des enfants. Soulignant l’importance d’analyser l’enseignement et l’apprentissage de la littératie dans des contextes formels et informels, les résultats présentent des informations sur la manière dont les futurs enseignants élaborent leur compréhension et situent leur identité professionnelle (Gee, 1990, 2000-2001) à l’aide du soutien à l’apprentissage. Les implications pédagogiques pour la formation des futurs enseignants sont exposées.